2018
DOI: 10.2147/opth.s157501
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity, endothelial cell density and polymegathism after iris-fixated lens implantation

Abstract: PurposeThe purpose of this study was to evaluate the visual acuity as well as endothelial cell density (ECD) and polymegathism after iris-fixated lens (Artiflex® AC 401) implantation for correction of moderate to high myopia.Patients and methodsIn this retrospective cross-sectional study, 55 eyes from 29 patients undergoing iris-fixated lens implantation for correction of myopia (−5.00 to −15.00 D) from 2007 to 2014 were evaluated. Uncorrected visual acuity, best spectacle-corrected visual acuity, refraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
3
5
1
Order By: Relevance
“…The results of this study were nearly or slightly less than the results reported by Nassiri et al [7] , where, 55 eyes from 29 patients with a refractive error of [−5 to −15 D] were included in the study. The average age of patients was 24.9 years with a range of 20-39 years.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The results of this study were nearly or slightly less than the results reported by Nassiri et al [7] , where, 55 eyes from 29 patients with a refractive error of [−5 to −15 D] were included in the study. The average age of patients was 24.9 years with a range of 20-39 years.…”
Section: Discussioncontrasting
confidence: 67%
“…Loss of pigment cells from the iris could also be due to excessive wall shear stress due to changes in the fluid dynamics of the anterior chamber. Secondary glaucoma is possibly caused by increasing the resistance to the flow of aqueous humor, either within the anterior chamber or at the outflow [7] .…”
Section: : [A] Baikoff Lens and [B] Nuvita Lensmentioning
confidence: 99%
“…Doors et al [18] in 2012 published the results of the multicentric European prospective study of 115 eyes of 73 patients, followed 6 months with an initial SE of −7.10 (2.70), which were obtained in 99% of patients, with the UCDVA >20/40 in 74.5%. Nassiri et al [19] in 2018 in a retrospective study of 55 eyes of 29 patients followed 6 months, the UCDVA was 20/25 or better in 81.5% of the cases. The results of Hashemi et al [20,21] in a study with 53 eyes of 28 patients with sphere −10.22 ± (3.02) were that 72.2% of the eyes had 20/25 or more vision and the safety and efficacy [24][25][26][27] are coincident with our work, especially in the first and second year.…”
Section: Discussionmentioning
confidence: 91%
“…Concerning the Artiflex/Veriflex pIOL, a study done by Dick et al 14 to assess the ECD of 290 eyes implanted with Artiflex pIOL for two years, reported a mean EC loss of 0.05%, 1.79%, and 1.07% at six months, one, and two years respectively. In another study by Nassiri et al 15 55 eyes underwent Artiflex lens implantation for correction of myopia, there was no statistically significant change in the ECD after six months of follow-up. The opposite was reported by Jonker et al 2 They reported chronic EC loss of 10% over 5 years in eyes implanted with the Artiflex myopic pIOL.…”
Section: Discussionmentioning
confidence: 86%